Keefektifan Model Pembelajaran Creative Problem Solving terhadap Kemampuan Berpikir Kreatif Berbantuan Mind Mapping - Veronica Septian; Zulmi Roestika Rini (Departement of Mathematics Education, 2024)
This research aims to determine the effectiveness of the Creative Problem Solving (CPS) learning model on the ability to think creatively with the help of mind mapping. This type of research is a quasi-experimental design in the form of the non-equivalent control group design. The population in this research are all MI Al Mustajab students. The sampling technique uses a non-probability sampling technique which is taken by purposive sampling. The research sample was classes IIIA and IIIB at SDIT Cahaya Ummat. Data collection techniques in this research are test and non-test techniques. The test technique uses pretest and posttest while the non-test technique uses observation, questionnaires and documentation. Data analysis techniques include normality test, homogeneity test, one way anova test, simple linear regression test, independent sample t test and paired sample t test. The results of the research show: (1) There is a difference in the use of the Creative Problem Solving (CPS) learning model assisted by mind mapping on creative thinking abilities, as evidenced by the significance level of 0.003 < 0.05 using the independent t test (2) There is an influence of the use of the Creative Problem learning model Solving (CPS) assisted by mind mapping on creative thinking, proven by a significance level of 0.000 < 0.05 using a simple linear regression test (3) There is an increase in the Creative Problem Solving (CPS) learning model assisted by mind mapping on creative thinking, proven by the level of significance, namely 0.000 < 0.05 using the paired sample t test. The conclusion of this research is the Creative Problem Solving (CPS) learning model assisted by mind mapping on students' creative thinking abilities.